Shaping Green Investment Pathways to Accelerate Sustainable Development Goals (SDGs) Achievement in Indonesia - Nurul Hasanah; Moh. Bahrul Ulum; Firman Floranta Adonara; Khoidin Khoidin (Rechtenstudent, 2026)
The transformation toward sustainable development requires the renewal of the investment law system so that it aligns with environmental, social, and economic principles as mandated in the Sustainable Development Goals (SDGs). This study analyzes the direction of green investment law formation in Indonesia through three main focuses: the existing regulatory framework, juridical barriers in its implementation, and the ideal normative model to strengthen the legal resilience of sustainable investment. The results show that green investment regulations remain sectoral and fragmented across various laws, such as the Investment Law, the Environmental Protection Law, and technical policies like the OJK Green Taxonomy. This fragmentation creates legal uncertainty, overlapping authorities, and gaps between technocratic policies and formal legal norms. These obstacles are exacerbated by weak institutional coordination, the absence of a legal definition of green investment, and the lack of binding incentive and supervision mechanisms. This study recommends the establishment of a lex specialis on green investment, strengthening the legal status of the Green Taxonomy, creating an integrated green licensing system, and reinforcing ecological protection obligations as a mechanism for intergenerational justice. Therefore, the formation of a comprehensive and integrated green investment legal framework is necessary to create legal certainty, enhance the attractiveness of sustainable investment, and strengthen Indonesia’s commitment to achieving the SDGs.